Impact of tumor-to-nipple distance on outcomes in robotic nipple-sparing mastectomy and reconstruction - Joon Suk Moon; Young Jin Lee; Tae Kyung Yoo; Jisun Kim; Il Yong Chung; Beom Seok Ko; Hee Jeong Kim; Jong Won Lee; Byung Ho Son; Sae Byul Lee (Discover Oncology)
Abstract Background Nipple-sparing mastectomy (NSM) has become a preferred surgical option for breast cancer patients due to its oncologic safety and aesthetic benefits. Robotic NSM (RNSM) offers enhanced precision and minimally invasive access, yet its feasibility in cases with a tumor-to-nipple distance (TND) ≤ 1 cm remains unclear. This study evaluates the oncologic safety and surgical outcomes of RNSM in patients with TND ≤ 1 cm by comparing it with both RNSM in patients with TND > 1 cm and conventional NSM (CNSM) in patients with TND ≤ 1 cm. Methods A retrospective analysis of 1427 patients who underwent NSM with immediate reconstruction between October 2020 and October 2023 was conducted. Propensity score matching (PSM) was applied to compare three groups: TND ≤ 1 cm, RNSM vs. TND > 1 cm, RNSM and TND ≤ 1 cm, RNSM vs. TND ≤ 1 cm, CNSM. Oncologic safety was assessed by analyzing subareolar resection margin status, while surgical outcomes included postoperative complications such as nipple-areolar complex (NAC) necrosis. Result After PSM, no statistically significant differences were observed in subareolar resection margin results or the incidence of adverse events between the TND ≤ 1 cm and TND > 1 cm RNSM groups. Similarly, no significant differences were found in oncologic or surgical outcomes between RNSM and CNSM in patients with TND ≤ 1 cm. Conclusions RNSM is a safe and feasible option for patients with TND ≤ 1 cm, achieving oncologic outcomes comparable to CNSM in patients with TND ≤ 1 cm and RNSM in patients with TND > 1 cm. These findings suggest that TND ≤ 1 cm should not be a contraindication for RNSM. Further prospective studies with long-term follow-up are necessary to validate these results.